2014
DOI: 10.3727/096368914x678562
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Implantation of Autologous Peripheral Blood Stem Cells in Stroke Patients: A Randomized Phase II Study

Abstract: In our previous study, intracerebral implantation of peripheral blood stem cells (PBSCs) improved functional outcome in rats with chronic cerebral infarction. Based on this finding, a randomized, single blind controlled study was conducted in 30 patients [PBSC group (n = 15) and control group (n = 15)] with middle cerebral artery infarction confirmed on a T2-weighted MRI 6 months to 5 years after a stroke. Only subjects with neurological deficits of intermediate severity based on the National Institute of Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 38 publications
0
92
0
1
Order By: Relevance
“…Several clinical studies have been reported which evaluated transplantation of other types of cells into basal ganglia of chronic motor stroke patients with similar characteristics to our study [27][28][29][30][31]. One was bone-marrow derived cells genetically modified to transiently overexpress Notch-1 protein [27].…”
Section: Potential Mechanism Of Therapeutic Actionmentioning
confidence: 75%
“…Several clinical studies have been reported which evaluated transplantation of other types of cells into basal ganglia of chronic motor stroke patients with similar characteristics to our study [27][28][29][30][31]. One was bone-marrow derived cells genetically modified to transiently overexpress Notch-1 protein [27].…”
Section: Potential Mechanism Of Therapeutic Actionmentioning
confidence: 75%
“…For both circulating and resident BM hematopoietic stem/progenitor cells, CD34 positivity has been exploited to develop relatively simple methods for purification using immunomagnetic selection (12). Clinical safety and feasibility for these purified cells has been demonstrated for some medical problems, including refractory severe aplastic anemia (13), stroke (14), critical limb ischemia (15,16), nonischemic dilated cardiomyopathy (17), liver cirrhosis (18,19), and myocardial infarction (20,21). CD34 + cells are an attractive option for revascularization therapy because they are rapidly mobilized from the BM into the peripheral blood after injury (22)(23)(24) and then home to the site of tissue damage and contribute to vascular repair and angiogenesis (25)(26)(27).…”
mentioning
confidence: 99%
“…In Stage 3, to answer Aims 2 and 3, we have conservatively proposed a further 18 participants, which is in keeping with the numbers (range 5-18) used in previous Phase 1 clinical trials of stem cell therapy administered by intracranial injection for ischemic stroke. 18,24,33 Based on preclinical meta-analysis data with an effect size of 40% 16 at least 50 participants would be needed to investigate efficacy of stem cell therapy with 80% power at a significance level of 0.05. We propose that a firstinhuman Phase 1 clinical trial on large numbers of participants is unethical until we determine treatment safety and feasibility.…”
Section: Sample Size Estimatesmentioning
confidence: 99%